IMPACT OF PUBLIC TRANSPORTATION SYSTEMS ON THE EPIDEMIC THREAT SPREADING: RESEARCH REVIEW AND ANALYSIS - Райда, Ігор (Modern engineering and innovative technologies, 2024)
Public transport systems are one of the factors in the spread of epidemic threats. Moreover, the use of public transport carries the risk of spreading the epidemic due to direct contact of passengers with each other in passenger transport vehicles during